Wettability alteration and IFT reduction during carbonated water injection; a critical investigation into the role of pH - Zoha Dalal Isfehani; Jalal Fahimpour; Mohammad Sharifi; Hossein Khalili; Mohammad Saeid Tayebi (Journal of Petroleum Exploration and Production Technology)
Abstract Carbonated water injection (CWI) is regarded as an effective technique for enhanced oil recovery (EOR) and CO2 sequestration. While wettability alteration and interfacial tension (IFT) reduction are widely recognized mechanisms for enhancing oil recovery CWI, their underlying processes are not yet fully understood. Gaining insight into these processes is essential for optimizing EOR strategies, improving predictive models, and enhancing CO2 sequestration. Consequently, this study experimentally investigates the variation in IFT and rock wettability during CWI at pressures of 500, 1200, and 2700 psi, with a constant temperature of 38 °C, using pendant drop and sessile drop methods. In addition to carbonated water, an aqueous solution with different adjusted pH was also employed to specifically examine the effects of pH on these phenomena. Contact angle measurements showed that lowering the pH of brine solutions from 7 to 1.5 shifts rock wettability from oil-wet (158.5°) to water-wet (64.2°). Zeta potential measurements confirmed that decreasing pH changes the oil/water interface’s surface charge to positive, leading to a repulsive force between the rock/brine and oil/brine interfaces, reducing oil-wetness. However, this change is temporary, as wettability reverts to oil-wet when pH returns to neutral, indicating that alteration is driven by the reversible expansion of the electric double layer in low-pH solutions. In contrast, exposure of oil-wet carbonate rock to carbonated water (contact angle of 122.6°) results in a permanent transition to a water-wet state (50.7°) due to two combined mechanisms of electric double layer expansion and mineral dissolution by the carbonic acid buffer system. There is a reduction in IFT from approximately 24 to 12 dynes/cm, when pH decreases from 7 to 2. This reduction is attributed to the ionization of the oil’s basic components, which act as natural surfactants, while the acidic components remain neutral. Consequently, the effectiveness of IFT reduction in the presence of carbonated water relies on the crude oil’s composition, particularly the ability of its basic components to ionize and become active. Thus, the results depict that the pH condition throughout the carbonated water injection can be applied as a correlating parameter for modeling and simulation purposes.